EFEKTIVITAS LAYANAN RAKYAT UNTUK SERTIFIKASI TANAH (LARASITA) DI KOTA MAKASSAR - Ismaniar Ismail (Jurnal Ilmiah Administrasita', 2017)
The purposeof this study was to analyze the effectiveness of the People Services for Land Certification (Larasita) in Makassar viewed from a process approach, which in cludes: service efficiency (time and cost), service procedures, coordination leader ship of subordinates, employee responsiveness and facilities. This type of researchis descriptive qualitative is give a proper explanation objective lyrelated to the actual state of the objectunder study. Types of data used consists of primary data is interviews and direct observationin the field and secondary data sourced from books, documents/ records/reports and legislation relating to the is suebeing investigated. From the results of research carried out showsthe implementation ofthe People's Service for Land Certification (Larasita) in Makassarless effective. This iscaused because the indicators of service efficiencyin terms of time, where the completion of the certification and implementation Larasita not in accordance with the provisions that have been made previously. This, compounded with the damaged condition of the infrastructure and the limitations that hinder the process of service Larasita. However, indicators of service procedures, coordination leaders of subordinate and responsiveness and employees canbe effective.